Que fronteiras para a UE? - Cavaco, Carminda (2004)
This article addresses the identity of Europe, the project and process of the construction of Europe, the successive enlargements and the mobility of external borders from the perspective of a Europe of variable geometries. It attempts to develop the discourse on the “return to Europe” for the Central and Eastern European Countries (CEEC), their movement towards democracy, their difficulties in entering the global market, EU assistance and new development dynamics. Then, the new enlargements for the short-term up to the Adriatic and the Black Sea, with the next countries to be admitted being Romania, Bulgaria and Croatia. Other notes are made on the possibility of other enlargements in the medium- to long-term, by setting the external borders farther to the East, towards Russia and the Caucasus, and to the Middle East, towards Turkey, and to the South, towards North Africa, countries that have a certain “desire for Europe”. The EU attracts with its status of post-modern empire, and it is necessary for Europe to stabilize and modernize its peripheries, without calling into question the EU’s project and with prejudice to strengthening the integration process.